Upaya Sekolah Meningkatkan Profesionalitas Tenaga Administrasi Sekolah (TAS) di MAN 2 Kota Pekanbaru - Ghafardi, Ghafardi (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2022)
This study aims to determine; 1) The condition of the professionalism of the TAS at MAN 2 Pekanbaru City, 2) Efforts made by schools to improve the professionalism of TAS at MAN 2 Pekanbaru City, and 3) Factors that influence the professionalism of TAS at MAN 2 Pekanbaru City. This research was conducted from July to September 2021 using a descriptive qualitative approach. Qualitative research is data obtained from various sources using various data collection techniques (triangulation) and is carried out continuously until the data is saturated (Sudaryono, 2016: 243). The subjects of this research consisted of the principal and seven TAS MAN 2 Pekanbaru City. The data collection methods consisted of interviews, observation, and documentation. The results of this study revealed three findings that concluded; 1) TAS at MAN 2 Pekanbaru City is quite professional, the indicator is from the seven components of school administration activities that have been carried out by TAS, 2) The efforts made by TAS to improve their professionalism are; attending training and socialization about the school administration system, learning independently with the assistance of the principal, and the efforts of the head of MAN 2 Pekanbaru City to improve the professionalism of TAS, namely including TAS in training or training or socialization as well as internal coaching, 3) Factors that influence the professionalism of TAS at MAN 2 Pekanbaru City include motivation, leadership, work infrastructure, and work climate.